The Influence of Digital Parenting on Alpha Generation Pre-Teenagers Grade 6 in One of the Private Elementary Schools in Jambi City - Darwin, Charles; Widowati, Atri; Haryanto, Eddy (Papanda Publisher, 2025)
The rapid growth of technology has had a significant impact on the lifestyle of pre-teens, especially those belonging to the Alpha generation. This study explores the role of digital parenting in shaping the behavior and academic performance of sixth-grade students at Stella Maris Private Elementary School in Jambi City. Using a qualitative descriptive approach, data were collected through interviews with parents, teachers, and students. This study involved 4 sixth-grade students. The findings reveal that most parents apply a democratic parenting style, which allows children to explore digital media with appropriate guidance and boundaries. This method has proven effective in helping children balance digital exposure with academic responsibilities. Conversely, authoritarian and neglectful parenting styles are rarely applied due to their negative impact on children's emotional and social development. Permissive parenting, while offering freedom, tends to lead to a lack of discipline and declining academic performance. The study concludes that democratic parenting, when integrated with clear digital media usage rules, plays a crucial role in supporting the development of pre-teens in the digital era. Practical implications of these findings highlight the importance of parents' role in setting clear boundaries for digital media use, as well as adopting a parenting style that supports children's emotional, social, and academic development.